Chemoprophylaxis is Cost-Effective in Total Ankle Arthroplasty. Issue 2 (April 2022) - Martinazzi, Brandon J.; Kirchner, Gregory; Bonaddio, Vincenzo; Manto, Kristen M.; Stauch, Chris M.; Koroneos, Zachary; Aynardi, Michael C.; Juliano, Paul J.
Category: Ankle; Ankle Arthritis; Other Introduction/Purpose: The use of chemoprophylaxis to prevent thromboembolic complications following total ankle arthroplasty (TAA) is debated in the field of orthopaedics. The incidence of thromboembolic complications has been shown to vary within the literature, and some studies suggest that the incidence may be similar to what is seen following hip and knee arthroplasty. Therefore, some surgeons will prescribe chemoprophylaxis, such as aspirin 325mg or enoxaparin 40mg following surgery, especially in high-risk patients. To our knowledge, the cost-effectiveness of chemoprophylaxis in TAA has not been investigated. This article presents a break-even analysis for chemoprophylaxis in TAA for the prevention of thromboembolic complications. Methods: The estimated cost of treating a thromboembolic complication ($9, 407.00) as well as the product cost of aspirin (325 mg) and enoxaparin (40 mg) were obtained from our institution's purchasing records. The high and low rates of thromboembolic complications were obtained from the literature. A break-even analysis was then performed to determine the absolute risk reduction (ARR) in thromboembolic complication rates to make chemoprophylaxis with aspirin 325mg and enoxaparin 40mg cost- effective. Results: The initial high rate of a thromboembolic complication following TAA was determined to be 9.8%. Costing $0.25, aspirin was considered cost-effective if the initial thromboembolic complication rate decreased by an ARR of 0.00266%, while enoxaparin (costing $131.73) was cost-effective if the initial rate decreased by an ARR of 1.40034%. For comparison, the initial low rate of thromboembolic complication following TAA was determined to be 0.45%. At this rate, aspirin was again considered to be cost- effective if the initial rate decreased by an ARR of 0.00266%. However, at this low rate, the ARR required to achieve cost- effectiveness for enoxaparin exceeds the initial thromboembolic complication rate. Conclusion: While the use of chemoprophylaxis following TAA is still being investigated, this break-even analysis demonstrates that aspirin is highly cost-effective for preventing thromboembolic complications. Furthermore, our results indicate that enoxaparin is cost-effective at the higher rates of thromboembolic complications, but cost-effectiveness is eliminated at a low rate. Not only does this break-even analysis demonstrate the cost-effectiveness of aspirin and, in some cases, enoxaparin, but the model can be easily applied to the values at any institution in order for orthopaedic surgeons to determine the cost-effectiveness of a therapeutic of their choice.